1996
DOI: 10.1159/000246297
|View full text |Cite
|
Sign up to set email alerts
|

Precipitating Factors and Associated Diseases in 84 Patients with Granuloma annulare: A Retrospective Study

Abstract: In a retrospective study including 84 patients, we assessed precipitating factors of granuloma annulare (GA) and asssociated pathologies. Fifteen per cent of the patients reported stress as an important trigger of GA, and in 10 patients (12%) we found an association between GA and diabetes mellitus: 3 latent, 4 type I and 3 type II. Eight of the diabetic patients presented multiple and 5 generalized GA. They suffered significantly more often from chronic relapsing GA than nondiabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
3
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 0 publications
3
69
3
7
Order By: Relevance
“…The association of GGA with DM is not yet clearly established. Studer et al 13 noted that 10 of 84 adult patients (12%) with GA (localized or generalized) had DM, as opposed to the 5% prevalence of DM among the regional population. However, other studies that looked for carbohydrate intolerance by performing glucose tolerance testing 4 or assessing the hemoglobin A1c values 14 failed to find an increased prevalence of altered carbohydrate metabolism in the patients with GA.…”
Section: Discussionmentioning
confidence: 99%
“…The association of GGA with DM is not yet clearly established. Studer et al 13 noted that 10 of 84 adult patients (12%) with GA (localized or generalized) had DM, as opposed to the 5% prevalence of DM among the regional population. However, other studies that looked for carbohydrate intolerance by performing glucose tolerance testing 4 or assessing the hemoglobin A1c values 14 failed to find an increased prevalence of altered carbohydrate metabolism in the patients with GA.…”
Section: Discussionmentioning
confidence: 99%
“…Studer et al found that 12% (10/84) patients with GA had diabetes. 5 These patients were significantly more likely to experience recurrent disease and 6/10 reported exacerbation of their skin with poor glycaemic control. A subsequent case control study found no association between type 2 diabetes and GA. 12 However, the control group used were patients with psoriasis, a condition now known to be associated with a number of comorbidities, including diabetes.…”
Section: Association With Diabetesmentioning
confidence: 99%
“…3,4 A variety of infectious agents have been implicated, including tuberculosis, Borrelia, varicella, EBV, hepatitis B and C and HIV. 4,5 Sun exposure and phototherapy with psoralen combined with ultraviolet A are also reported to precipitate GA. 4,6 Reported drug causes of GA included amlodipine, gold, allopurinol, diclofenac, quinidine, intra-nasal calcitonin and anti-tumour necrosis factor (TNF) agents. 6,7 In one study 15% of patients attributed onset of GA to psychological stress.…”
Section: Aetiologymentioning
confidence: 99%
See 2 more Smart Citations